Assessing N2O Emissions from Tropical Crop Cultivation in Mineral and Peatland Soils: A Review - Suwardi, Suwardi; Darmawan, Darmawan; Djajakirana, Gunawan; Sumawinata, Basuki; Al Viandari, Nourma (Universitas Sebelas Maret, 2023)
Nitrous oxide (N2O) emissions from agricultural activities contribute significantly to global warming. Understanding the factors influencing N2O emissions is crucial for developing effective mitigation strategies. This review assesses N2O emissions from various crops cultivated in tropical mineral and peatland soils, providing insights into the impact of land use, fertilization practices and rainfall on N2O fluxes. Field measurements of N2O fluxes were conducted in agricultural fields growing corn, peanuts, and cassava in Bogor Regency, West Java Province, as well as in peatland areas with Acacia plantations and natural primary forests in Bengkalis Regency, Riau Province. The study assesses the total N2O fluxes for each crop and land type, revealing significant variations in N2O emissions among different crops and land uses. Peatland areas exhibit higher emissions compared to mineral soils, emphasizing the need for targeted mitigation measures in these ecosystems. The findings highlight the importance of considering the type and age of land use when evaluating N2O emissions. Land management practices, such as fertilizer use and soil disturbance, emerge as critical factors affecting N2O emissions. Improper fertilizer application and excessive soil disturbance can lead to increased N2O emissions, underscoring the necessity for careful N fertilizer management and conservation tillage techniques.